PENERAPAN BACK-END APLIKASI E-ARSIP BERBASIS WEB MENGGUNAKAN PHP - Haq, Muhammad Raihan Izharul; Insany, Gina Purnama (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Kampus Merdeka Program initiated by the Ministry of Education, Culture, Research, and Technology provides opportunities for students to develop competencies beyond their study programs, including internships. The Statistics Indonesia (BPS) Sukabumi Regency Office is one of the institutions supporting this program by offering internships in the field of information technology. This article presents the development of a web-based Back-end application for the E-Arsip system at BPS Sukabumi. The application, developed using PHP, aims to implement a digital archiving system to enhance the efficiency of document management and centralized storage. The discussion covers the development stages, from database design to back-end implementation. The results indicate that the application has the potential to support more effective and efficient archive management within the BPS Sukabumi office.